THE POPULATION OF KASHKADARYA REGION'S ETHNIC COMPOSITION (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Region kashkadarya complete and accurate official data on the ethnic composition of the population has declared open in recent years, although not in the general scope and historical statistics of the republic ethnic-demographic sources, based on the following classification may be given: Region kashkadarya (Kashkadarya region) of the population in the republic of uzbekistan and in many respects the colorful ethnic regions.